Encyclopedia of Industrial Biotechnology 2014
DOI: 10.1002/9780470054581.eib661
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of Minerals by Acidophile Microorganisms

Abstract: In this article, we review the state of the art in the field of bioleaching applications for sulfide minerals, including beneficiation of copper, nickel, zinc, cobalt, uranium, and pyrite bearing gold and silver. A special emphasis is given to the specific acidophile microorganisms participating in the process, with insights into their particular physiology and also into the industrial applications being reported to date, such as dump and heap bioleaching, and stirred‐tank bioleaching. Some challenges are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…Mesophilic bioleaching constitutes an industrial practice for secondary copper sulfide ores, but not for primary copper sulfides such as chalcopyrite due to low copper recovery and slow kinetics. Recently, we have shown that heap bioleaching is economically feasible at industrial scale for lowgrade primary copper sulfide ores including bornite (Cu 5 FeS 4 ) and chalcopyrite (CuFeS 2 ) and even at run-of-mine (ROM) size by means of mesophilic inoculation [9]. Most former studies with pure primary copper sulfide high purity minerals have been done with concentrates added at low pulp densities in shake-flasks [2], optimal for homogeneous mixing and planktonic microbial growth, but certainly not for biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Mesophilic bioleaching constitutes an industrial practice for secondary copper sulfide ores, but not for primary copper sulfides such as chalcopyrite due to low copper recovery and slow kinetics. Recently, we have shown that heap bioleaching is economically feasible at industrial scale for lowgrade primary copper sulfide ores including bornite (Cu 5 FeS 4 ) and chalcopyrite (CuFeS 2 ) and even at run-of-mine (ROM) size by means of mesophilic inoculation [9]. Most former studies with pure primary copper sulfide high purity minerals have been done with concentrates added at low pulp densities in shake-flasks [2], optimal for homogeneous mixing and planktonic microbial growth, but certainly not for biofilm formation.…”
Section: Resultsmentioning
confidence: 99%